Louis Bromfield, Age Anxiety, and the End of the American Expatriate - Francescato, Simone (Oltreoceano - Rivista sulle migrazioni, 2024)
This article examines two early works by Louis Bromfield, a notable member of the American literary community in Paris in the first half of the 20th century. In the essay “Expatriate—Vintage 1927” Bromfield argues that notions such as “American expatriate” and “young American girl abroad” have become superseded, as they reflect an obsolete kind of internationalism. The same argument is fictionalized in the short story “The Apothecary”, where Bromfield reworks characters and plots of the transatlantic realist tradition to represent the intersection of an obsolete kind of internationalism with (gendered) age anxiety and creative exhaustion.